Efficacy of Elastodontic Devices vs. Clear Aligners in Lower Intercanine Distance Changes Assessed by Computer-Aided Evaluation - Eleonora Ortu; Davide Pietropaoli; Samuele Cova; Mario Giannoni; Annalisa Monaco (MDPI AG, 2023)
Background: This pilot study aimed to verify the efficacy of two orthodontic appliances in relation to changes in the lower intercanine distance in growing patients. Methods: Twenty patients aged 10-16 years were enrolled in the study and separated into test and control groups. The test group included 10 patients (5 males, 5 females; mean age, 10.4 ± 1.57 years) who were treated with an elastodontic device. The control group included 10 patients (5 males, 5 females; mean age 10.8 ± 1.53 years) who were treated with clear aligners. The two groups exhibited the same orthodontic features. The orthodontic criteria were: skeletal class I relationship, molar class I relationship, and presence of lower crowding. Patients were evaluated as having mild or moderate crowding according to the Daniels and Richmond index. The lower intercanine distance was evaluated at three timepoints via intraoral scans: T0 (before starting therapy), T1 (after six months), and T2 (after 1 year). Data were analyzed using a nonparametric approach via the Wilcoxon signed-rank test. Results: There was no statistically significant difference between the two groups at T0, T1, or T2 (p < 0.05). Conclusions: elastodontic devices and clear aligners can successfully help the orthodontist conduct lower arch expansion treatment. These appliances are comfortable to wear, simple to clean every day, and reduce the number of dentist appointments. Finally, but not of least importance, these devices have allowed dentists to continue orthodontic treatments during the lockdowns of the COVID-19 pandemic.